Code Switching and Code Mixing in Teaching-Learning Process - Ansar, Fithrah Auliya (Universitas Islam Negeri Raden Intan Lampung, 2017)
Many people speak and switch or mix their general use of language with their mother tongues, especially in communicating with people who understand the different languages. In English Language Teaching classrooms, code switching comes into use either in the teachers’ or the students’ discourse. Generally our students whose formal learning in Indonesia, their first language is Indonesian and learning second language just in the class. And when talking each other in the class, in English learning they often resort to a swithched and mixed code (Indonesia-English). The use of the elements of English is sometimes unconscious. It is also same with the teacher. Teacher sometimes conciously and unconciously make a switching and mixing the languages in providing knowledges.Code-switching and code-mixing are well-known traits in the speech pattern of the average bilingual in any human society the world over, where both of them are the most obvious and widespread which used at different language. Through observing the use of code switching and code mizing in teaching-learning process in Indonesia, the reader can understand the functions, types, and reasons in using the swithing and mixing the languages.